1997
DOI: 10.1111/j.1741-2358.1997.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

A reference guide to drugs and dry mouth – 2nd edition

Abstract: Xerostomia (dry mouth) is an uncomfortable and potentially harmful oral symptom which is usually caused by a decrease in the secretion rate of saliva (salivary gland hypofunction, or SGH). It is more prevalent in the elderly population, primarily due to their increased use of drugs and their susceptibility to disease. Many drugs and drug classes have been linked to xerostomia; the xerogenic effect increases when many drugs are taken concurrently. This Reference Guide to Drugs and Dry Mouth is designed to allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
203
1
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(226 citation statements)
references
References 29 publications
6
203
1
16
Order By: Relevance
“…Rad et al (2013, Kerman) (3) reported that the prevalence of xerostomia in 1010 Kermanian subjects in Iran was 55%.They evaluated subjective xerostomia while we investigated objective xerostomia. The result of the Sreebny et al (16) study was in accordance with that of the present study and the prevalence of xerostomia was 40%. Unlike the present study, other researches on the prevalence of oral dryness in general population showed that it can be detected in up to 46% of the people (17).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Rad et al (2013, Kerman) (3) reported that the prevalence of xerostomia in 1010 Kermanian subjects in Iran was 55%.They evaluated subjective xerostomia while we investigated objective xerostomia. The result of the Sreebny et al (16) study was in accordance with that of the present study and the prevalence of xerostomia was 40%. Unlike the present study, other researches on the prevalence of oral dryness in general population showed that it can be detected in up to 46% of the people (17).…”
Section: Discussionsupporting
confidence: 82%
“…Orellana (13) and Murray Thomson et al (9) achieved similar results too. Although in our study the influence of bronchodilators on xerostomia was more noticeable, other studies often have pointed that tranquilizers and antidepressants caused xerostomia (7,10,16). Analgesics had a minimum effect in xerostomia occurrence in our study; however, the results of Thomson et al study (9) showed that an analgesic's role in xerostomia occurrence was significant.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…13 Cannabis consumption has been associated with a reduction in salivary flow and may lead to oral problems like progressive dental caries, fungal infection, oral pain, and dysphagia. 14,15 The main psychoactive ingredient of Cannabis sativa, D9-tetrahydrocannabinol (THC), affects different physiological functions. Twenty five years ago, two subtypes of G-proteincoupled cannabinoid (CB) receptors were identified: the CB1 central receptor subtype, which is mainly expressed in the brain, 16,17 and the CB2 peripheral receptor subtype, which appears to be particularly abundant in the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…A tablet that is swallowed will be subjected to GIT peristalsis in the presence of relatively large volumes of digestive fluids secreted throughout the GIT, facilitating tablet disintegration and drug dissolution. In the SL cavity, tablets are exposed to minimal physiological agitation; moreover, a limited volume of saliva, 0.3 mL/min resting flow rate up to 1 mL/min stimulated flow rate (5), is available to facilitate tablet disintegration and drug dissolution. Currently, the available pharmacopeias' dissolution apparatuses and methods (6)(7)(8)(9) do not simulate these unique characteristics for testing rapidly disintegrating SL tablets.…”
Section: Introductionmentioning
confidence: 99%